KONSEP PENGEMBANGAN MUTU PENDIDIKAN BERBASIS MADRASAH - Sakir, Moh (IAIN Ponorogo, 2012)
Abstract: Along with the change of educational management paradigm from centralized to decentralized system, every school is given a wide range of opportunities to establish and develop its own potential resources to improve the quality of education. As part of the national education system, Madrasah is inevitably demanded to transform itself into a better quality in response to the aforementioned change in order to be able to compete with public schools. Hence, the managers of Madrasah or Islamic schools must be aware that the power-based approach that they have employed is not relevant anymore to cope with the needs of the rapid change in our educational system. For this reason, it is essential to accommodate a myriad of constructive ideas from various parties for the improvement of Madrasah. In accord to this, Madrasah-based or Islamic-based school management is obviously required with regard to the professionalism and contextual-rational paradigm by applying the bottom-up model in deciding the policies. Besides, human resources management should also be adjusted professionally basing on the academic competency standards with the restriction of personal interest. Furthermore, it requires the development of sustainable curriculum so as to adjust the improvement of science and technology.